Entrepreneurial Tendencies among People with ADHD - Dimic, Nebsjsa; Orlov, Vitaly (Senate Hall, 2015)
This paper studies the impact of people having attention deficit hyperactivity disorder (ADHD) on their predisposition toward entrepreneurship. We employ hand-collected survey data and psychometric tests to study the relationship between ADHD and occupational choice. The results of regression analysis suggest that ADHD sufferers have a significantly higher marginal probability of being entrepreneurs, while ADHD does not affect the likelihood of being a wage earner or being unemployed. Moreover, people with ADHD exhibit significantly higher values in the entrepreneurial tendency measures relative to others. By exploring the determinants of entrepreneurial tendencies, we find that ADHD affection has a positive impact on many entrepreneurial characteristics. Furthermore, we find that the significance of the ADHD variable maintains in the presence of entrepreneurship and demographic controls. Overall, these findings highlight the importance of the ADHD community as a rich source of entrepreneurs. Keywords: entrepreneurial tendencies, psychology and economics, entrepreneurship
Keywords: entrepreneurial tendencies|psychology and economics|entrepreneurship